Mathematical Ability in Terms of Socioeconomic Status and Mathematical Self-Efficacy - Nurdiana Siregar; Nurkhairunnisa Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to examine students' mathematical abilities in algebra and numbers and then these abilities are viewed from socioeconomic status and mathematical self-efficacy. This study uses a descriptive design that will be examined by PGMI students at a state university in North Sumatra. The data was obtained by looking at the scores from the students' mathematical ability tests, the scores from the questionnaires and the mathematical self-efficacy scale. Data were analyzed using descriptive analysis techniques using the normal curve approach. The results showed that 1) the mathematical abilities of students who had low, medium, and high socioeconomic status were classified as the same for each category with low results, 2) the mathematical self-efficacy of students who had high and moderate had low mathematical abilities.